2018
DOI: 10.29313/mimbar.v34i2.3650
|View full text |Cite
|
Sign up to set email alerts
|

Social Experience and Trust on Prisoners and Non-Prisoners

Abstract: Trust is shaped by the role of personal interaction in social experience, including past experiences, individual knowledge of events experienced by close people, and exposure to information from the community. Based on this paradigm, individuals who are formed with different experience, knowledge, and information will have different trust. Aiming to examine the paradigm, this study investigated the differences of trust in two groups of participants with different experiences, i.e. prisoners (n= 68) and non-pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…There are other factors that can drive someone to commit corruption as noncooperative behaviour either psychological or non-psychological aspect. Rosiana, Djunaidi, Setyono, & Srisayekti (2018) found that a reliance on corruption perpetrator's institution is classified as lower than one who did not commit corruption. Beside reliance on the institution, other psychological factors can affect to corruption, namely big five personalities and motivation (Abidin & Siswadi, 2015).…”
Section: Others Factor In Corruptionmentioning
confidence: 98%
“…There are other factors that can drive someone to commit corruption as noncooperative behaviour either psychological or non-psychological aspect. Rosiana, Djunaidi, Setyono, & Srisayekti (2018) found that a reliance on corruption perpetrator's institution is classified as lower than one who did not commit corruption. Beside reliance on the institution, other psychological factors can affect to corruption, namely big five personalities and motivation (Abidin & Siswadi, 2015).…”
Section: Others Factor In Corruptionmentioning
confidence: 98%
“…Metode pengambilan data dengan cara menyebarkan 2 kuisoner dalam bentuk googleform kepada responden mahasiswa. Dalam mengukur Institutional Trust peneliti menggunakan alat ukur Rosiana (Rosiana et al, 2018a), dan bertujuan untuk melihat kepercayaan individu kepada 22 lembaga-lembaga pemerintah Indonesia. Peneliti melakukan modifikasi dengan bantuan expert judgement untuk menambahkan 1 item yang sesuai dengan konsep teori instititutional trust.…”
Section: B Metodologi Penelitian Institutional Trustunclassified
“…Contoh item : Seberapa percaya anda terhadap kementrian Kesehatan pada masa pandemi. Kuesioner pada alat ukur ini menggunakan skala likert karena akan mengukur sikap dan dibagi menjadi 5 (lima) pilihan jawaban yaitu sangat tidak setuju, tidak setuju, ragu-ragu, setuju, dan sangat setuju (Rosiana et al, 2018a).…”
Section: B Metodologi Penelitian Institutional Trustunclassified
“…Trust Trust is the basic capital to be able to work together with others (Rosiana et al, 2018). This is trust between actors involved in the development of halal tourism in carrying out their roles and responsibilities.…”
Section: The Potential For Inclusivity In Alamendah Villagementioning
confidence: 99%